Catalytic production of high-value chemicals from biomass-derived products (2024)
The world's population growth and the increasing demand for energy have driven the search for renewable energy sources, in line with the United Nations Sustainable Development Goals (SDGs) for Responsible Consumption and Production. Biorefineries emerge as fundamental alternatives to conventional refineries, focusing on biomass conversion for the sustainable production of chemicals. This thesis addresses the challenge of diversifying energy sources and the production of valuable chemicals by exploring thermal catalysis over four different chapters.